2020
DOI: 10.14475/kjhpc.2020.23.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Spiritual Needs of Terminal Cancer Patients and Their Primary Family Caregivers

Abstract: This study was conducted to examine differences in Spiritual Interests Related to Illness Tool (SpIRIT) scores and the degree of spiritual needs (SNs) between patients with terminal cancer and their primary family caregivers and to compare spiritual needs between them. Methods: The study participants were inpatients with terminal cancer and their primary family caregivers at 40 national hospice centers. The final analysis included 120 SpIRIT surveys from patients and 115 from family members, and 99 SNs questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Second, the McSCTP-HPCTs is tied to spiritual needs with expressions, spiritual issues, and MCI based on the attributes of spirituality. In studies investigating the spiritual needs of patients who require hospice care and their families in South Korean culture [ 27 , 40 ], spiritual needs—grounded in the spirituality of patients and their families—were all high in the order of interconnectedness, meaning, and religious demands. Further, in a study on perceptions of spiritual care among patients with life-threatening cancer, primary family caregivers and hospice nurses [ 41 ] demonstrated that spiritual care is commonly seen as relating to having the opportunity for internal reflection, finding meaning, encouraging hope, and listening to and being with patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the McSCTP-HPCTs is tied to spiritual needs with expressions, spiritual issues, and MCI based on the attributes of spirituality. In studies investigating the spiritual needs of patients who require hospice care and their families in South Korean culture [ 27 , 40 ], spiritual needs—grounded in the spirituality of patients and their families—were all high in the order of interconnectedness, meaning, and religious demands. Further, in a study on perceptions of spiritual care among patients with life-threatening cancer, primary family caregivers and hospice nurses [ 41 ] demonstrated that spiritual care is commonly seen as relating to having the opportunity for internal reflection, finding meaning, encouraging hope, and listening to and being with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we narrowed down the 12 spiritual issues depicted in the ISPEC guidelines [ 6 ] to nine issues suitable for South Korean culture, centered around meaning (“despair/hopelessness” and “lack of meaning and purpose [existential]”), interconnectedness (“anger at God or others,” “guilt/shame,” “grief/loss,” “reconciliation,” and “abandonment by God or others/isolation”), and transcendence (“concerns about one’s relationship with a deity” and “conflicted or challenged belief systems”). We excluded two spiritual topics (“religious-specific”, and “religious/spiritual struggle”) and merged two issues (“abandonment by God or others” and “isolation”) because of cultural differences based on the spiritual needs assessment [ 27 , 28 ]. This suggests that the framework and content of spiritual care training should consider variations according to cultural differences, but still follow global standard guidelines [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A needs assessment was conducted as follows. First, we identi ed the spiritual care needs of patients with lifethreatening illness and their families who were admitted to hospice palliative care institutions in Korea [26]. Among their spiritual care needs, the desire for love and connection, nding meaning, and hope and peace were found to be higher than religious beliefs.…”
Section: Stage I: Development Analysismentioning
confidence: 99%
“…12,20,21 The concept of hope also has a spiritual aspect that provides an intrinsic resource for individuals to express and achieve their goals, especially in uncertain, critical, and stressful situations. [22][23][24] Spiritual well-being is especially important for parents in coping with stressful situations and challenging experiences such as childhood cancers throughout the entire cancer trajectory, and is among the factors that positively affect parents' level of hope. 25,26 It has been identi ed in the literature that there is a positive relationship between spiritual well-being and the hope levels of parents of children diagnosed with cancer.…”
Section: Introductionmentioning
confidence: 99%